2013
DOI: 10.1007/s11434-013-5756-8
|View full text |Cite
|
Sign up to set email alerts
|

In-situ cosmogenic 36Cl denudation rates of carbonates in Guizhou karst area

Abstract: This study quantifies surface denudation of carbonate rocks by the first application of in-situ cosmogenic 36 Cl in China. Concentrations of natural Cl and in-situ cosmogenic 36 Cl in bare carbonates from Guizhou karst areas were measured with isotope dilution by accelerator mass spectrometer. The Cl concentration varied from 16 to 206 ppm. The 36 Cl concentrations were in range of (0.8-2.4)10 6 atom g −1 , resulting in total denudation rates of 20-50 mm ka −1 that averaged over a 10 4 -10 5 a timescale. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…Matsushi et al (2010) showed the importance of chemical dissolution in karst areas under subtropical climates in Japan and the greater impact of physical erosion in subarctic environments. Xu et al (2013) came to similar conclusions studying samples collected in various climatic contexts in China and whose sampling altitudes ranged from 500 to 2300 meters above sea level. They determined denudation rates varying from 17 to 47 mm/ka that are roughly inversely proportional to the Mean Annual Temperature (MAT) at the sampling sites.…”
Section: -Development and Applications Of Cosmogenic Nuclides In Carbsupporting
confidence: 61%
“…Matsushi et al (2010) showed the importance of chemical dissolution in karst areas under subtropical climates in Japan and the greater impact of physical erosion in subarctic environments. Xu et al (2013) came to similar conclusions studying samples collected in various climatic contexts in China and whose sampling altitudes ranged from 500 to 2300 meters above sea level. They determined denudation rates varying from 17 to 47 mm/ka that are roughly inversely proportional to the Mean Annual Temperature (MAT) at the sampling sites.…”
Section: -Development and Applications Of Cosmogenic Nuclides In Carbsupporting
confidence: 61%
“…Xu et al. () found similar denudation rates in the Guizhou karst, China (MAP 900–1,300 mm). Both studies obtained denudation rates with similar ranges to that of our dataset in the Luberon where MAP is 700 mm, which highlights the importance of water availability and chemical dissolution in controlling carbonate weathering, as proposed by Ryb, Matmon, Erel, Haviv, Benedetti et al.…”
Section: Discussionmentioning
confidence: 76%
“…Most of these studies have focused on areas dominated by quartz‐rich bedrock, due to the routine use of in‐situ 10 Be to determine denudation rates. In contrast, only a few studies have used 36 Cl to investigate the denudation in carbonate‐dominated landscapes (Matsushi et al., ; Stone, Allan, Fifield, Evans, & Chivas, ; Xu et al., ). Recent work by Ryb, Matmon, Erel, Haviv, Benedetti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Stone et al () first established the use of the 36 Cl cosmogenic nuclide to determine bedrock denudation rates in limestones. Previous studies of 36 Cl denudation rates have focused on exposed bedrock denudation rates, where dissolution is the dominant lowering process (Godard et al, ; Schaller et al, ; Thomas et al, ; Xu et al, ). However, quantification of carbonate denudation at the catchment scale is needed to integrate the effects of mechanical denudation processes along hillslopes and channels and to understand its impact on relief generation.…”
Section: Introductionmentioning
confidence: 99%
“…Note that carbonate lithologies are disproportionately over-represented at high elevations. Xu et al, 2013). However, quantification of carbonate denudation at the catchment scale is needed to integrate the effects of mechanical denudation processes along hillslopes and channels and to understand its impact on relief generation.…”
Section: Introductionmentioning
confidence: 99%